Workshop Pengelolaan SDM Di Era Digital Dalam Pembangunan Desa Sijungkang Kabupaten Tapanuli Selatan - Tiur Lona, Rina; Maya Mei Shanty Lubis, Ade; Harahap, Rosina; Latif Lubis, Abdul; Hasibuan, Muallim (COVIT (Community Service of Tambusai), 2023)
One way to develop a region is to have quality Human Resources (HR). To realize this, several things are often done, namely through guidance, training and education. Sijungkang Village, South Tapanuli Regency, is one of the district government assisted villages. In order for the village to develop, as academics, the community service team conducted a workshop on HR management in the digital era. The purpose of this activity is to improve the quality of human resources, especially MSMEs in Sijungkang village so that they are able to face the challenges of information technology development and are able to improve the local economy. The service method is carried out through lectures and simple training on good human resource management and training in the use of digital-based technology through social media. Based on the results of interviews and questionnaires during the implementation of the community service, it was found that the enthusiasm of the participants was very good, the participants were interested in following things that were useful. This activity provides a solution in the proper use of social media and increases participants' knowledge and understanding of the importance of digital-based science today. Kata Kunci: Workshop, HR, Digital Era, Development